he History Of The Debus Tradition In The Malay Community In Ujung Kubu Village, Batu Bara Regency - Alizah, Nur (Pena Cendekia Insani, 2022)
The debus tradition that developed in 1722, which at that time was used to fight against Dutch colonialism and to scare the Dutch from entering the territory to be colonized, so that people did things that made no sense to the Dutch, such as cutting their heads off even because of the attractions that made sense. This made the Dutch afraid and would not come again to the area they wanted to colonize. Debus is a village art from the edge of the stronghold which is one of the martial arts and includes elements of sound, dance, so that this tradition of debus was used to fight the Dutch and is now turning into public entertainment.